Principles of Financial Management - Ofili, Ugwudioha M. (Kaduna, Nigeria : M. O. Press, 2018)
This book covers the principles, techniques and methods involved in financial management theories and practice.
Includes bibliographical references and index.
ijb, 12/02/2020
Loans
Keywords: Financial management